COVID-19線上教學教師情緒勞務對自我效能感影響之研究-以教學正念為調節變項 The Influence of Online Teaching Emotional Labor on Teacher Self-Efficacy During COVID-19: The Moderator of Mindfulness - 謝傳崇 Chuan-Chung Hsieh; 李慧潔 Hui-Chieh Li; 張羿涵 Yi-Han Chang; 陳雨然 Yu-Ran Chen (National Taiwan Normal University, 2024)
本研究旨在瞭解在COVID-19線上教學期間教師情緒勞務中的淺層展現與深層展現對自我效能感的影響，並檢視教學正念於淺層展現與深層展現對自我效能感影響關係的調節效果。研究方法為問卷調查法，研究對象為於新冠疫情期間具線上教學經驗之臺灣國小教師，有效樣本為644份。研究使用多元迴歸分析進行假設檢驗。研究結果發現，因COVID-19疫情採線上教學期間，教師淺層展現程度愈高，則自我效能感愈低；教師深層展現程度愈高，則自我效能感愈高，本研究進一步發現教學正念對深層展現影響自我效能感的加乘效果不顯著、正念程度高的教師在進行淺層展現時對自我效能感的降低程度與正念程度低的教師無顯著差異。本研究建議學校聘請專家進行教師情緒調控之培訓課或鼓勵教師參與相關研習課程，多採深層展現進行教學，提升教師自我效能感。 Introduction Following its outbreak in 2019, the COVID-19 pandemic caused a considerable shift in work patterns across multiple industries. Taiwan continued education through online platforms, maintaining a "no suspension of classes" approach to ensure uninterrupted teaching and student learning. However, this transition imposed challenges on teachers, many of whom faced substantial stress and anxiety due to the demands of online teaching. Accordingly, this study focused on emotional labor, specifically surface acting and deep acting, as antecedent variables. During online teaching, teachers must maintain a strong belief in and enthusiasm for teaching to effectively foster student engagement and learning outcomes. The present study selected teacher self-efficacy as its outcome variable and explored the effects of surface acting and deep acting on teacher self-efficacy in the context of online teaching. The relevant literature suggests that mindfulness in teaching can enhance the effectiveness of teaching strategies and mitigate emotional exhaustion in teachers, thereby warranting its inclusion as a moderating variable in this study. Relevant studies have indicated that surface acting in emotional labor diminishes individual well-being and lowers self-efficacy, whereas deep acting enhances individual well-being and increases self-efficacy. Furthermore, deep acting positively predicts classroom management self-efficacy, whereas surface acting negatively affects such self-efficacy. However, these findings are based on traditional face-to-face teaching methods and lack support from empirical research regarding the relationships among teachers' surface acting, deep acting, and self-efficacy during the online teaching period prompted by the COVID-19 pandemic in Taiwan. Additionally, understanding of the moderating role of teaching mindfulness in the relationships among surface acting, deep acting, and teacher self-efficacy remains limited. Accordingly, this study aimed to determine (1) how teacher surface acting and deep acting influence teacher self-efficacy in the context of online teaching during the COVID-19 pandemic and (2) the moderating role of teaching mindfulness in the relationships among teacher surface acting, deep acting, and self-efficacy. Research Purpose This study examined how teacher emotional labor affected teacher self-efficacy during the online teaching period prompted by the COVID-19 pandemic in Taiwan and investigated the moderating role of teaching mindfulness in the relationship between teacher emotional labor and self-efficacy. The aim of this study was to clarify the differential effects of surface acting and deep acting on teacher self-efficacy in the context of online teaching. The results of this study are expected to contribute to practical implications for teaching and to suggest timely support and assistance for teachers engaged in online teaching in order to enhance overall teaching effectiveness within school organizations. Data Collection The present research methodology conducted a questionnaire survey targeting primary school teachers in Taiwan with experience of online teaching during the COVID-19 pandemic period. A total of 644 valid responses were collected. The study utilized an English scale from an internationally published journal. To ensure conceptual validity and to avoid any loss of meaning due to translation, a back-translation process was employed. In addition, adjustments were made to some wordings to suit the context of online teaching during the COVID-19 pandemic, and relevant explanations were added accordingly. This study employed the emotional labor scale developed by Diefendorff et al. (2005) to assess teacher surface acting and deep acting during online teaching in the pandemic period. The measurement tool for surface acting consisted of seven items, whereas the measurement tool for deep acting consisted of four items. The Teacher Self-Efficacy Scale developed by Tschannen-Moran and Hoy (2001) was employed to assess self-efficacy among teachers engaged in online teaching. This scale contains three dimensions- namely "Teaching Strategies" (four items), "Classroom Management" (four items), and "Student Engagement" (four items)- yielding a total of 12 items. The Mindfulness in Teaching Scale developed by Frank et al. (2016) was employed to assess teacher mindfulness. This scale comprises eight items across two dimensions: "Intrapersonal Mindfulness" (six items) and "Interpersonal Mindfulness" (two items). Data Analysis IBM SPSS Statistics version 20.0 was used to perform quantitative statistical analysis of the survey data. The data analysis methods utilized in this study included descriptive statistics, Pearson correlation, and multiple regression analysis. Multiple regression analysis was employed to examine how surface acting and deep acting influenced teacher self-efficacy and to investigate the moderating effects of teaching mindfulness. Results The study results revealed that during the period of online teaching prompted by the COVID-19 pandemic, higher levels of surface acting among teachers were associated with lower self-efficacy, whereas higher levels of deep acting were associated with higher self-efficacy. Furthermore, the moderating effect of teaching mindfulness on the relationship between deep acting and self-efficacy was not significant. Finally, no significant difference was found in the reduction of self-efficacy between teachers with high levels of mindfulness who engaged in surface acting and those with low levels of mindfulness. Recommendations At the school level, organizational culture can substantially affect teachers' emotional labor. Organizations can enhance the substance of a teacher's job structure while fostering a school culture based on mutual trust and support. These actions are particularly crucial in the context of online teaching, where support for teachers' instructional efforts is even more essential. Hiring experts to conduct training or relevant workshops related to emotional regulation for teachers can empower educators to apply their professional knowledge to develop personalized emotional expression skills. Such skill development can, in turn, improve teachers' foundational ability to control their emotions and thus align with external expectations regarding their educational goals. In the context of online teaching, supporting teachers in managing their emotions appropriately and effectively by using emotional labor strategies is crucial for enhancing the effectiveness of online teaching. Suggestions for Future Research Future research should incorporate genuine emotional expression into strategies for emotional labor. Although this study analyzed only teachers from primary schools in Taiwan, it did not specifically analyze numbers of teachers in different regions. Accordingly, future research could investigate the distribution of teachers on the basis of the geographical locations of the primary schools where they teach. Because teachers are embedded within schools and because each school may have unique resources and methods of supporting online teaching, teachers from a single school often share certain common traits. Future research could utilize hierarchical linear modeling to explore relationships among variables at different levels.